2008
DOI: 10.1007/s00417-008-0915-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of variants in the VEGF gene on progression of proliferative diabetic retinopathy

Abstract: The AA genotype at -2578C/A polymorphism in the VEGF gene is associated with proliferative diabetic retinopathy. No significant association with -634 C/G polymorphism was confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 25 publications
2
47
1
8
Order By: Relevance
“…The meta-analysis showed that -634C/G polymorphism C allele and genotypes CC vs CG + GG and CG vs CC + GG had no statistically significant association with DR. The result further verified most former results [13][14][15][16][17][18][19][20][21] . Meta-analysis is a summary analysis method that can combine various similar research results.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The meta-analysis showed that -634C/G polymorphism C allele and genotypes CC vs CG + GG and CG vs CC + GG had no statistically significant association with DR. The result further verified most former results [13][14][15][16][17][18][19][20][21] . Meta-analysis is a summary analysis method that can combine various similar research results.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, VEGF5'-untranslated region-634C/G polymorphism is an independent risk factor in DR. However, further studies on the association yielded similar [9][10][11][12] and opposite results [13][14][15][16][17][18][19][20][21] . Even in one country without ethnic diversity, different results were obtained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Одним из ключевых факторов в прогрессировании ДР признан фактор роста эндотелия сосудов (VEGF) [52].…”
Section: интравитреальное применение ингибиторов Vegfunclassified
“…1 206 ) являются продуктами одного гена, образующимися в результате альтернативного сплайсинга мРНК. В гене VEGF выявлены полиморфные позиции -634, +936, -2578; обнаружены взаимосвязи ва-риантов нуклеотидов в этих позициях с риском развития диабетической ретинопатии (ДР) в разных этнических группах [12][13][14][15]. По нашим данным [16,17], для больных СД 2 типа (СД2) свойственны комбинации гомозиготных вариантов VEGF 2578CC, 936CC, генов интерлейкинов и матриксных металлопротеиназ: IL4 590СС, IL6 174GG, IL10 592СC и 1082АА, TNFА 238GG, 308GG и 863СC, MMP-2 1306CC и ММР-9 1562СС.…”
Section: обоснование применения анти-Vegf терапии при дмоunclassified